Sternum. Ontogenesis, anatomicvariants, anomaliesand practical importance - Grigorescu Sido, Francisc; Zimmermann, Anca; Matei, Adela (Medicine and Pharmacy Reports, 2014)
Based on 132 sternums from human subjects, ages between 5th fetal month and 89 years, the article presents anatomic variants of sternum, the value of substernal angle, the relationship with the internal thoracic vessels etc. The advances in genetics, imaging and thoracic surgery, especially in the last 30 years, explain the attention concerned to the sternum’s anatomy and its variants (no article published in local literature and few in the international literature). Presenting the sternum’s development enables the understanding of anatomic variants appearance and of several pathologic conditions of the region (sternal fissures, pectus excavatum, pectus carinatum, asternia with cutaneous aplasia, complex syndromes: Cantrell, Currarino-Silverman etc.). Some anatomo-clinical correlations (imaging and surgical) are presented as well.